For equals only : race, equality, and the equal protection clause - Botts, Tina Fernandes (Philosophy of race, 2018)
This book philosophically explores changing conceptions of race and equality in Supreme Court decisions interpreting the Equal Protection Clause since the enactment of the 14th Amendment. It traces these changing conceptions alongside the gradual elimination of the social equality of racialized persons from the Supreme Court's list of priorities.